Antioxidant and Antibacterial Activity of Selected Indonesian Honey against Bacteria of Acne - Shafira Ananda Djakaria; Irmanida Batubara; Rika Raffiudin (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
Honey has natural bacteriostatic and bactericide activities; thus, it could be active compounds as an antibacterial against Propionibacterium acnes, the main bacteria in acne forming state. Our study aims to determine phenolic and flavonoid contents (qualitative and quantitative), antioxidants, along with antibacterial activity against P. acnes of selected Indonesian honey. Honey used in this study, including honeybees and stingless bees, were collected from Sumbawa, Riau, Belitung, Sukabumi, Banyuwangi, Bogor, and South Sulawesi. In the method, the quantitative content of phenols and flavonoid were measured using a spectrophotometer. Further, DPPH (2, 2’-diphenylpicryl hydrazyl) and ABTS (2’-azino-bis (3- ethylbenzothiazoline-6-sulfonic acid) assays were used to measure the antioxidant activities, and subsequently microdilution method was applied to determine antibacterial activity. The results showed that Indonesian honey contains phenolics and flavonoids in the range of 49.5-67.3 μg Gallic Acid Equivalent (GAE)/g and 766.5-1509.5 μg Quercetin Equivalent (QE)/g, respectively. All honey samples also show antioxidant and antibacterial activities. Of note, Apis cerana honey from Banyuwangi has the highest antioxidant and antibacterial activity compared to others. It has the Inhibition Concentration (IC50), Trolox Equivalent Antioxidant Capacity, Minimum Inhibitory Concentration (MIC) and Minimum Bactericide Concentration (MBC) values of 59.85 mg/L, 122 μg Trolox/g, 125 mg/mL, and 500 mg/mL respectively. Our study reveals that Indonesian honey can inhibit and kill P. acnes as well. Nonetheless, the phenolic content of honey is not always linear with antioxidant and antibacterial activities.